2021
DOI: 10.1097/qai.0000000000002663
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential Impact of Disruptions Due to COVID-19 on HIV Among Key and Lower-Risk Populations in the Largest Cities of Cameroon and Benin

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Models suggested that substantial increases in HIV related mortality by up to 40% are expected in next years in sub-Saharan Africa due to severe interruption of ART [15]. A mathematical model by researchers from Cameroon and Benin estimated that, in the worst-case scenario, a 6-month interruption of ART initiation and 50% reduction in HIV prevention/treatment use, would disproportionately impact key populations (especially female sex workers) with an increase of HIV incidence (+50%) and related deaths (+20%) over one year [22]. Moreover, several reports have predicted increases in mother-to-child HIV transmission rates and HIV drug resistance [15].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Models suggested that substantial increases in HIV related mortality by up to 40% are expected in next years in sub-Saharan Africa due to severe interruption of ART [15]. A mathematical model by researchers from Cameroon and Benin estimated that, in the worst-case scenario, a 6-month interruption of ART initiation and 50% reduction in HIV prevention/treatment use, would disproportionately impact key populations (especially female sex workers) with an increase of HIV incidence (+50%) and related deaths (+20%) over one year [22]. Moreover, several reports have predicted increases in mother-to-child HIV transmission rates and HIV drug resistance [15].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…The DRC government also took precautions to avoid supply stock shortages despite shutdown activities and border restrictions. For example, the movement of residents was not restricted within each province, but was restricted between provinces [ 25 , 26 ]. Other studies have shown positive outcomes of MMD because it reduced barriers to access to ART facilities (such as transportation and time off from work) and prevented the overcrowding of clinics, thus reducing the risk of COVID-19 transmission as well [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential effects of disruption to HIV programs and CoT in sub-Saharan Africa caused by COVID-19 were forecasted to result in increases in mortality risk, most notably due to the disruption to the supply of ART resulting in an individual’s discontinuation of ART [ 26 ]. In addition to a six-month interruption of ART supply, other disruption scenarios included reduced outreach and access to clinics, which was expected to cause a decrease in ART initiations, HIV testing, and the proportion of PLHIV that are VL suppressed [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study using data from Cameroon and Benin, a 6-month disruption in ART initiation and a 50% reduction in the provision of HIV prevention/treatment was projected to increase HIV incidence by 50% and HIV-related deaths by 20%. 22 Similarly, a modeling study using Chinese data showed that the overall impact of COVID-10 on HIV incidence and HIV-related deaths depend on which services are disrupted and the intensity and duration of impairments. 23 …”
Section: Discussionmentioning
confidence: 99%